2023
DOI: 10.21203/rs.3.rs-2914400/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attributed Network Embedding Model for Exposing COVID-19 Spread Trajectory Archetypes

Abstract: The spread of COVID-19 revealed that transmission risk patterns are not homogenous across different cities and communities, and various heterogeneous features can influence the spread trajectories. Hence, for predictive pandemic monitoring, it is essential to explore latent heterogeneous features in cities and communities that distinguish their specific pandemic spread trajectories. To this end, this study creates a network embedding model capturing cross-county visitation networks, as well as heterogeneous fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Beside the previously mentioned methods, knowledge graph embedding techniques to encode the entities and relations in a knowledge graph as dense and low-dimensional vector representations are utilized in the literature of SARS-CoV-2 [62,63]. In addition, functional data analysis following the principle of "breaking up the whole into pieces" of big data analysis to transfer discrete and high-frequency sequences of data to continuous smooth functions, treating the whole functions as a single entity with an internal unified structure, is used in the literature [64].…”
Section: Methods [Source] Explanationmentioning
confidence: 99%
“…Beside the previously mentioned methods, knowledge graph embedding techniques to encode the entities and relations in a knowledge graph as dense and low-dimensional vector representations are utilized in the literature of SARS-CoV-2 [62,63]. In addition, functional data analysis following the principle of "breaking up the whole into pieces" of big data analysis to transfer discrete and high-frequency sequences of data to continuous smooth functions, treating the whole functions as a single entity with an internal unified structure, is used in the literature [64].…”
Section: Methods [Source] Explanationmentioning
confidence: 99%
“…Human mobility datasets have been widely used in multiple hazards, including hurricane [32][33][34][35] , ooding [36][37][38][39][40][41] , and infectious diseases [42][43][44][45] . These studies have found human mobility data was useful to understand people's reaction to hazards 46,47 .…”
Section: Introductionmentioning
confidence: 99%